Clinical and Kidney Structural Characteristics of Living Kidney Donors With Nephrolithiasis and Their Long-term Outcomes. Issue 1 (January 2022) - D'Costa, Matthew R.; Merzkani, Massini A.; Denic, Aleksandar; Mullan, Aidan F.; Larson, Joseph J.; Kremers, Walter K.; Park, Walter D.; Alexander, Mariam P.; Chakkera, Harini A.; Taler, Sandra J.; Erickson, Stephen J.; Stegall, Mark D.; et al.
Abstract : Background: Nephrolithiasis in living kidney donors is concerning due to the potential impact on long-term postdonation kidney function. Methods: We performed a cohort study of living kidney donors from 2 centers with a baseline computed tomography scan and implantation renal biopsy. Donors (>5 y since donation) completed a follow-up survey or underwent chart review to assess eGFR and incident hypertension. Stone formers were classified as symptomatic if they had a past symptomatic episode or asymptomatic if only incidental radiographic kidney stones were identified during donor evaluation. We compared baseline clinical, imaging, and biopsy characteristics by stone former status including review of metabolic evaluations in stone formers. Long-term risks of renal complications (low eGFR and hypertension) by stone former status were evaluated. Results: There were 12 symptomatic and 76 asymptomatic stone formers among 866 donors. Overall, baseline clinical characteristics and implantation biopsy findings were similar between stone formers and non-stone formers. After a median follow-up of 10 y, stone former status was not associated with eGFR <60 mL/min/1.73 m2, eGFR <45 mL/min/1.73 m 2, or hypertension. Conclusions: Both asymptomatic and symptomatic SF have favorable histology findings at baseline. Long-term kidney outcomes were favorable in select stone formers with no evident increased long-term risk for decreased kidney function or hypertension after donation.